Mediating Roles of Helping Behavior Between Self-Efficacy and Work Engagement Towards Technical and Social Performance - Tarman Budianto (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2022)
Several empirical studies have shown that helping behavior results in dysfunctional employees, such as stress, role overload, and the emergence of work-family conflict because of the time and energy that is allocated to helping others. However, other literature shows that helping behavior is considered an act of kindness that can result in high performance evaluations. This study aims to examine whether the helping behavior variable has a mediating role in the relationship between self-efficacy and work engagement towards technical and social performance. This study involved 261 widyaiswara (trainer) in Indonesia. Data analysis using bootstrapping technique. The results showed that helping behavior mediate in the relationship between: (1) self-efficacy and technical performance, (2) self-efficacy and social performance, (3) work engagement and technical performance, (4) work engagement and social performance. These findings validate and provide new empirical evidence that helping behavior has a positive impact on performance. Based on these findings, future research is recommended to explore further the influence of helping behavior in reducing relationship conflict, because conflict-free organizations never exist. These findings, practically can be a guide for leaders in improving performance, both technical performance and social performance, namely by increasing work engagement and self-efficacy, so that helping behavior can contribute to the achievement of employee performance and organizational goals.